The improvement of the basics units of cooperative production into the actualization of Cuban economical model - Villegas Chádez, Rubén (REVESCO. Revista de Estudios Cooperativos, 2017)
Created twenty two years ago, Basics Units of Cooperative Production (UBPC) have left their track in the productive weave of Cuban agriculture. Is undeniable the contribution these productive units have made to the resistance of national economy in front of the worst crisis that the country faced after the triumph of the Revolution, contribution that was not too significant about production and efficiency, but it was very important on the financial field because they took on great part of the cost of the named “adjustment without desocialization”. The UBPC did not fulfilled the expectation in relation to solution of agro alimentary problem of the country and, on the matter of economical efficiency, we´re still waiting that de exception will became rule. In 2011 were approved 17 steps to untie the autonomous and efficient performance of UBPC, however neither these steps got success. The objective of present work is to demonstrate how important the UBPC are as antecedent and reference point for the expansion of cooperativism in Cuba, especially for experimental process of constitution of non agricultural cooperatives (CNoA). This process goes through the perfection of UBPC and the experiment of CNoA, however it doesn´t take in account, in its amplitude, the fortitudes and debilities of the cooperativism of State in our country. It is necessary in order to guarantee that the approved lineaments lead to fortify socialist sector and not his dialectic contrary: the capitalist sector of economy. The predominant economicism in management of these cooperatives by the state institutions and by the own members of cooperatives, who have given priority to their individual and collective interests in short time, have systematically limited the positive impact of these cooperatives on satisfaction of the social needs that is, after all, the highest objective of actualization of our economical model.
Keywords: Cooperative; Basics Units of Cooperative Production (UBPC); non agricultural cooperatives (CNoA); cooperativism of State; property